The influence of differences in learning habits and management of children's mentoring time on the formation of children's character - Ratna Nurdiana (Journal of diversity in learning (JDIL), 2021)
Education makes a great contribution to a country. One of the indicators of education is learning, the success of children's learning can be seen through children's learning habits, while what happens to children aged 6-12 years do not know how to put themselves in the learning time and how to learn, it can be seen from several environmental factors that are around it. Children's learning habits in their sense is the learning behavior of a child from time to time in the same way, in order to increase the knowledge both at school and at home can facilitate the success of the child in learning. Based on the statement, researchers are interested in examining the link between children's learning habits and the formation of children's characters. With the attitude in the indicator of character formation of the child will be able to influence the learning habits of the child better, as well as the existence of learning the habits of children who have several indicators, including how to learn and learning time will build the formation of the character of the child to be researched. This research is included in descriptive research aims to describe, explain and validate the social phenomena that become the object of research, Descriptive research method is narrative research used in qualitative or qualitative research design. Based on the ongoing research of several theories and frames of thinking above, Based on ongoing research, the hypothesis proposed in this study is "There is an Influence of Children's Learning Habits and Character Building".